Enhancing Science Learning Experience and Social Attitudes through Vygotsky’s Social Reconstruction Model with Scaffolding - Ni Nyoman Lisna Handayani; I Putu Suardipa; I Made Ari Winangun; I Ketut Ngurah Ardiawan (Universitas Pendidikan Ganesha, 2025)
Conceptual understanding of science is an essential component that students must possess in the learning process. However, elementary school students’ understanding of scientific concepts remains relatively low. This condition is partly caused by learning approaches that have not fully facilitated optimal social interaction and learning support. In addition, the limited development of students’ social attitudes also hinders the creation of meaningful learning experiences. This study aims to analyze the effect of Vygotsky’s social reconstruction model combined with scaffolding techniques on students’ science learning experiences and to examine the effectiveness of this model after controlling for the covariate of social attitudes. This research employed a quasi-experimental design with a posttest control group design. The participants consisted of 42 students divided into experimental and control groups. Data were collected using questionnaires to measure social attitudes and multiple-choice tests to assess science learning experiences. Data analysis was conducted using the ANCOVA statistical test to determine the effects and covariate contributions to learning outcomes. The results revealed that the Vygotsky social reconstruction model with scaffolding techniques had a significant effect on students’ understanding of scientific concepts, with a covariate contribution of social attitudes amounting to 65.1%. These findings indicate that the implementation of a learning model grounded in social interaction and gradual support can enhance conceptual understanding while fostering positive social attitudes among elementary students. The implication suggests that teachers should systematically integrate the social reconstruction approach with scaffolding strategies in science instruction to create a more collaborative, reflective, and meaningful learning process.